Pre-Hospital Factors Influencing the Provision of Acute Care for Patients with Stroke: Preliminary Findings from A State-Wide Data Linkage Study - Eliakundu, Amminadab; Smith, Karen; Kilkenny, Monique; Kim, Joosup; Bagot, Kathleen; Andrew, Emily; Bladin, Christopher; Cadilhac, Dominique (International Journal of Population Data Science, 2020)
Introduction Improvement in access to reperfusion therapy and reductions in treatment delays requires coordination of multiple systems and services including a well-organised and streamlined pre-hospital care system. Objectives and Approach Our objective is to examine pre-hospital and hospital factors that influence long-term outcomes in patients with stroke. We linked and merged patient-level data from the Australian Stroke Clinical Registry (AuSCR) to Ambulance Victoria (AV), hospital administrative datasets (Victorian Admitted Episodes Data; VAED) and emergency department data (Victorian Emergency Minimum Dataset; VEMD) using probabilistic, iterative methods. Logistic regression models were used to determine clinical factors associated with access to evidence-based treatments. Results 7,373 episodes in the AuSCR were available for linkage, of which 4,569 (62%) were matched with AV records (58% male, median age 72 years). Of these 4,569 matched records, 4,159 (58% male, median age 73 years) had a record in the VAED or VEMD. Stroke or transient ischaemic attack was suspected for 68% of patients by paramedics based on the AV data. Highest transport priority was used for 64% of patients. Patients suspected of stroke by paramedics were more likely to be treated in stroke unit (unadjusted odds ratio, 1.72; 1.47, 2.01) and more likely to receive thrombolysis if ischaemic stroke (unadjusted odd ratio: 4.64, 3.47, 6.20). Conclusion/Implications Linkage of these administrative data with the AuSCR provide the opportunity to interrogate a range of questions to inform policy and practice of acute stroke care. Future analyses will investigate patient (such as comorbidities), clinical and system factors that influence provision of evidence-based care for patients with stroke and whether these influence outcomes at 6 months after stroke.